2023
DOI: 10.3390/jpm13050789
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Incidence of Postoperative Acute Kidney Injury Following the Administration of Remimazolam or Sevoflurane in Elderly Patients Undergoing Total Knee Arthroplasty: A Randomized Controlled Trial

Abstract: Background: We evaluated the incidence of postoperative acute kidney injury (AKI) and complications when remimazolam (RMMZ) or sevoflurane (SEVO) were used in elderly patients undergoing total knee arthroplasty. Methods: Seventy-eight participants aged ≥65 were randomly allocated to either the RMMZ or SEVO group. The primary outcome was the incidence of AKI on postoperative day (POD) 2. The secondary outcomes included intraoperative heart rate (HR), blood pressure (BP), total drug administered, emergence time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In a previous study, the time to extubation after cessation of remimazolam decreased to a value comparable to that after sevoflurane cessation. [20] There was a previous study by Sekiguchi et al [21] comparing remimazolam and propofol during the induction of anesthesia in middle-aged and elderly patients, and no significant difference of hemodynamics were observed between those who administered remimazolam and propofol. There are several difference between the study by Sekiguchi et al and this study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a previous study, the time to extubation after cessation of remimazolam decreased to a value comparable to that after sevoflurane cessation. [20] There was a previous study by Sekiguchi et al [21] comparing remimazolam and propofol during the induction of anesthesia in middle-aged and elderly patients, and no significant difference of hemodynamics were observed between those who administered remimazolam and propofol. There are several difference between the study by Sekiguchi et al and this study.…”
Section: Discussionmentioning
confidence: 89%
“…In a previous study, the time to extubation after cessation of remimazolam decreased to a value comparable to that after sevoflurane cessation. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported DEX-induced bradycardia ( 46 , 47 ). Studies have also reported that there is less reduction in HR when RMMZ is administered than that with the administration of other anesthetic drugs ( 48 , 49 ). Similar results were obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Following the removal of 35 duplicate records through automated and manual methods, an additional 41 records were excluded after reviewing their titles and abstracts, as they did not meet the inclusion criteria. Upon reviewing the full-text articles of the remaining records, we excluded 13 studies for various reasons: they were not randomized controlled trials [32][33][34][35][36][37], did not set up a propofol group [38,39], did not have routine flumazenil usage in the remimazolam group [19,[40][41][42], or did not have outcomes we wanted [43]. Ultimately, nine studies meeting the criteria were included [44][45][46][47][48][49][50][51][52].…”
Section: Search and Selectionmentioning
confidence: 99%